Reinforced and toughened polyolefin material as well as preparation method and application thereof

By introducing modified silica and styrene-modified polypropylene into polypropylene and modifying silica with β-cyclodextrin derivatives, the problems of low notch sensitivity and impact strength of polypropylene materials are solved, and the rigidity and toughness balance and low temperature performance of the material are improved.

CN119708742AActive Publication Date: 2025-03-28PETROCHINA CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311271637.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

Polypropylene (PP) materials have high notch sensitivity and low impact strength, and are particularly poor in low temperature conditions, which limits their further promotion and application.

Method used

By introducing modified silica and styrene-modified polypropylene into polypropylene, the silica is modified with β-cyclodextrin derivatives, and its dispersion and cross-linking reaction in polypropylene are improved to enhance the rigidity and toughness of the material.

Benefits of technology

The bending elastic modulus and the impact strength of the simple-supported beam are significantly improved, the performance of the material under low temperature conditions is improved, and its wide range of applications and applicability in high-end fields is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708742A_ABST
    Figure CN119708742A_ABST
Patent Text Reader

Abstract

The invention discloses a reinforced and toughened polyolefin material as well as a preparation method and application thereof. The polyolefin material comprises the following raw materials in parts by weight: 75-95 parts of modified polypropylene A, 1-20 parts of modified silicon dioxide B and 1-7 parts of an auxiliary agent, wherein the modified polypropylene A is modified by a grafting monomer, and the structural formula (I) of the grafting monomer is # imgabs0 #, in the formula (I), X is linear alkyl or saturated fatty alcohol group containing 1-10 carbon atoms, or X is not contained; the surface of the modified silicon dioxide B is modified with a cyclodextrin derivative. According to the invention, the inclusion effect of the cyclodextrin derivative on organic molecules is utilized, and through the host-guest reaction between the cylindrical molecule beta-cyclodextrin and the benzene ring, the polypropylene molecular chain is cross-linked, and the phase interface interaction force is strengthened, so that the polyolefin material has excellent rigid-tough balance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a reinforced and toughened polyolefin material and a preparation method and application thereof. Background Art

[0002] Polypropylene (PP) has good comprehensive mechanical properties, heat resistance, chemical resistance, insulation, molding and processing performance, and low density, and its cost is relatively low, so its application range is very wide. The application areas of PP include automotive parts, electrical accessories, chemical equipment, building materials, insulation materials, packaging materials, textile materials, fishing nets, daily necessities, etc. The application areas of PP are still expanding year by year, and its output growth rate has been the first among general plastics in recent years. However, PP has high notch sensitivity and low notch impact strength, especially at low temperatures, which greatly limits the further promotion and application of polypropylene. Therefore, strengthening and toughening PP has gradually become the focus of research at home and abroad.

[0003] When the inventors selected inorganic nanomaterials to modify polyolefins, they found that due to the small particle size, large specific surface area, strong surface adsorption and large surface energy of the nanomaterials, when the nanoparticles are used directly, the agglomeration problem will cause the modification efficiency to be significantly reduced. In practical applications, it is necessary to modify the surface of the nanoparticles to avoid agglomeration and agglomeration of the nanoparticles, so as to improve their dispersibility and rheological properties.

[0004] There are two main methods of increasing the capacity reported in the relevant literature: (1) treating the surface of nano-silicon dioxide; (2) adding an interfacial compatibilizer on the basis of surface treatment of nano-silicon dioxide. The treatment methods of nano-silicon dioxide include surface coating, adsorption modification, coupling agent treatment, surface grafting, etc. The surface hydroxyl content of nano-silicon dioxide particles is high, and it is easy to react with organic matter containing functional groups. If the organic matter has antioxidant and anti-aging properties, it can also give the composite material special properties such as anti-aging. Among them, the combination of coupling agent treatment and surface grafting of organic polymers is currently a hot topic of research. (China Plastics, 2012, 26, 11-16).

[0005] Commonly used coupling agents and grafted organic substances are silane coupling agent and polymethyl methacrylate (PMMA), styrene monomer (St), polybutyl acrylate (PBA), etc., to prepare SiO 2 -g-PMMA, SiO 2 -g-St、SiO 2 -g-PBA and other modified silica particles. Adding SiO 2 -g-PMMA can effectively improve the tensile strength, flexural strength and Rockwell hardness of PP, and the effect is better than that of unmodified nano-SiO 2 However, due to the poor impact toughness of PMMA, it has a great influence on the impact properties of the matrix and is closely related to SiO2 After connection, the product is promoted to form heterogeneous nucleation, and the toughness is greatly lost under the condition of increased rigidity. In addition, PMMA is a casting material. Compared with extrusion preparation, the solvent bonding time is longer, the bonding strength is lower, the preparation cost is high, and it is easy to form cracks in solutions and chemicals. The common method of PP toughening is to introduce elastomers (POE, EMMA, etc.) to blend or use cross-linking (DA reaction) reaction. The above methods have poor consideration for the rigidity and toughness balance performance of the PP matrix, which is one of the important research and development directions of high-end PP products.

[0006] Patent 201610321080 discloses a method for preparing a silica-modified polypropylene material. After the silica is modified with a silane coupling agent, it reacts with an organic acid with multiple hydroxyl groups (branching effect) and an alkyl acid without hydroxyl groups (end-capping effect) to organically modify the surface of the silica. The interface bonding force between the silica powder and polypropylene after modification by this method is enhanced, so that the prepared composite material has good mechanical properties. The silica modification process described in this technology needs to be carried out in a high temperature environment (120-140°C), a nitrogen atmosphere, a catalyst (p-toluenesulfonic acid), etc., and the reaction conditions are relatively harsh.

[0007] Patent 201410151479 discloses a method for preparing high-flow and impact-resistant polypropylene, wherein the raw materials include the following components: homopolymer polypropylene, ethylene-propylene block copolymer and processing aid are mixed, mixed evenly in a high-speed mixer, and the mixture is melt-extruded and granulated in a twin-screw extruder to obtain high-flow and high-impact polypropylene. The base resin of this technology uses homopolymer polypropylene, which does not contribute enough to the impact performance of the composition, and it is difficult to achieve a joint improvement of MFR and impact strength. If the impact strength is to be further improved, the melt flow rate will be greatly affected.

[0008] Patent 201680053228 discloses a high-impact polypropylene-based blend. This technology improves the impact resistance by introducing polystyrene or its copolymer into the polypropylene resin. The resulting blend has an impact strength of more than 25 kJ / m 2 This technology introduces polystyrene into the polypropylene matrix. Since the two resins are completely incompatible systems, the blend has severe phase separation and needs to be improved by introducing a graft copolymer as a compatibilizer.

[0009] Patent CN111909482A discloses a modified high temperature resistant polypropylene material and its preparation method. First, propylene monomer, styrene, acrylonitrile, maleic anhydride, and modified silica are used to prepare modified polypropylene through multi-stage reactions. Then, modified silica is prepared from β-cyclodextrin, silica, and dibutyltin dilaurate. Finally, glass fiber is added to further enhance the heat resistance and strength of polypropylene. The obtained resin has the characteristics of high temperature resistance and high mechanical strength. This method uses a variety of modifiers, and the preparation process is complicated. In addition, the dispersibility of inorganic fillers such as silica and glass fiber in the matrix resin is difficult to control, and they are easy to agglomerate, resulting in decreased mechanical properties. Summary of the invention

[0010] In order to at least partially solve the above technical problems existing in the prior art and further enrich the modification methods for toughening and strengthening polyolefin materials, the present invention provides a polyolefin material with high strength and good rigidity-toughness balance, which can be applied to more and higher-end fields.

[0011] As one aspect of the present invention, it relates to a reinforced and toughened polyolefin material, which comprises the following raw materials by weight: 75-95 parts of modified polypropylene A, 1-20 parts of modified silicon dioxide B, and 1-7 parts of an auxiliary agent;

[0012] The modified polypropylene A is modified by a grafting monomer, and the structural formula (I) of the grafting monomer is:

[0013]

[0014] In formula (I): X is a linear alkyl group containing 1 to 10 carbon atoms or a saturated fatty alcohol group, or does not contain X;

[0015] The surface of the modified silica B is modified with a cyclodextrin derivative.

[0016] In one or some possible embodiments, the grafting monomer is styrene, and the mass content of the styrene in the modified polypropylene A is 0.2-3%; the cyclodextrin derivative is a β-cyclodextrin derivative, and the mass content of the β-cyclodextrin derivative in the modified silica B is 0.5-5%.

[0017] By adopting the above technical scheme, the surface of modified silica B is β-cyclodextrin (βCD) with inclusion effect. βCD has a special annular hollow cylindrical structure. The hydroxyl groups are distributed at both ends and the outside of the cylinder, making it hydrophilic. The inside of the cylinder is hydrophobic. The modified SiO 2-g-βCD has good dispersibility in polypropylene materials due to its reduced surface tension. At the same time, the main chain of modified polypropylene A contains non-polar benzene ring side groups, which can enter the βCD cavity to form cross-links between polypropylene molecular chains, strengthen the product interface force, and make the prepared polyolefin material have excellent rigidity and toughness balance.

[0018] In one or some possible embodiments, the following raw materials are included by weight: 88-95 parts of modified polypropylene A, 5-7 parts of modified silicon dioxide B, and 4-5 parts of auxiliary agent;

[0019] The modified polypropylene A is obtained by modifying polypropylene with styrene, and the mass content of the styrene in the modified polypropylene A is 0.2-3%;

[0020] The surface of the modified silicon dioxide B is modified by a silane coupling agent and the beta-cyclodextrin derivative in sequence, and the mass content of the beta-cyclodextrin derivative in the modified silicon dioxide B is 0.5-5%.

[0021] In one or some possible embodiments, the polypropylene is homopolypropylene or copolymer polypropylene.

[0022] By adopting the above technical solution, on the one hand, the SiO 2 The dispersion of particles in the matrix can effectively enhance the SiO 2 The particles enhance the rigidity of the polypropylene material matrix; on the other hand, the introduction of cyclodextrin molecules causes the molecular chains of the polypropylene material to undergo cross-linking reactions, effectively improving the toughness of the product; finally, SiO 2 The introduction of g-βCD modified particles makes the polypropylene material matrix in SiO 2 Under the synergistic effect of βCD, the heterogeneous nucleation sites are increased, further improving the strength of the product.

[0023] In one or some possible embodiments, the melt flow rate (MFR) of the polypropylene is 30-110 g / 10 min.

[0024] In one or some possible embodiments, the copolymerized polypropylene is ethylene-propylene copolymer, and the mass content of the ethylene monomer in the copolymerized polypropylene is 5-15%.

[0025] In one or some possible embodiments, the mass content of the ethylene monomer is 8-10 wt%.

[0026] In one or some possible embodiments, the copolymerized polypropylene comprises ethylene-propylene random copolymer, ethylene-propylene block copolymer and isotactic polypropylene; the mass content of the ethylene-propylene random copolymer is 8-24%; the mass content of the ethylene-propylene block copolymer is 3-11%; the mass content of the isotactic polypropylene is 65-89%.

[0027] By adopting the above technical solution, the rubber phase can ensure that the matrix resin has a certain impact strength; the compatibilizing phase can enhance the interaction between the rubber phase and the resin matrix; and the isotactic phase can ensure the bending modulus of the matrix resin.

[0028] In one or some possible embodiments, the particle size of the ethylene-propylene random copolymer particles is 0.05 to 4 μm, and the density is 1×10 5 ~1×10 8 Pieces / mm 3 .

[0029] In one or some possible embodiments, the silane coupling agent is selected from one or more of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane;

[0030] The derivative of β-cyclodextrin is selected from one or more of hydroxyethyl-β-cyclodextrin, hydroxypropyl-β-cyclodextrin, amino-β-cyclodextrin, thiol-β-cyclodextrin, carboxymethyl-β-cyclodextrin and β-cyclodextrin.

[0031] In one or some possible embodiments, the auxiliary agent includes a halogen absorber and an antioxidant.

[0032] In one or some possible embodiments, the halogen absorbent is selected from one or more of hydrotalcite, calcium stearate, and zinc stearate.

[0033] In one or some possible embodiments, the antioxidant is a hindered phenol antioxidant or a compound antioxidant;

[0034] The compound antioxidant includes a main antioxidant and a secondary antioxidant; wherein the mass ratio of the main antioxidant to the secondary antioxidant is 1:(1-2).

[0035] In one or some possible embodiments, the primary antioxidant is a hindered phenol antioxidant; and the secondary antioxidant is a phosphite antioxidant.

[0036] As another aspect of the present invention, it relates to a method for preparing the above-mentioned enhanced toughened polyolefin material, the method comprising the following steps:

[0037] S1. Add modified polypropylene A, modified silicon dioxide B and additives in order by weight, mix well, and obtain a prefabricated material;

[0038] S2, extruding and granulating the prefabricated material in S1 to obtain a polyolefin material.

[0039] In one or some possible embodiments, in S1, the preparation of the modified polypropylene A includes: mixing the polypropylene, the styrene and the initiator to obtain a mixed modified polypropylene A.

[0040] In one or some possible embodiments, the mixing temperature is set to 180-190° C., the rotation speed is set to 40-50 rpm, and the mixing time is 5-10 min.

[0041] In one or some possible embodiments, in S1, the preparation of the modified silicon dioxide B comprises the following steps:

[0042] S11, placing nano-silicon dioxide in an activation solution to obtain activated nano-silicon dioxide;

[0043] S12, adding the activated nano-silica in S11 to a dilute acetic acid solution of a silane coupling agent to obtain nano-silica modified with a silane coupling agent;

[0044] S13, placing the nano-silica modified with a silane coupling agent obtained in S12 in a buffer solution containing a β-cyclodextrin derivative, and mixing them evenly to obtain modified silica B.

[0045] In one or some possible embodiments, in S11, the activation temperature of the activated nano-silica is 50-60° C., and the activation time is 1-2 hours.

[0046] In one or some possible embodiments, in S12, the mixing time of the activated nano-silica and the dilute acetic acid solution of the silane coupling agent is 2 to 4 hours.

[0047] In one or some possible embodiments, in S12, the mass ratio of the silane coupling agent to the activated nano-silica and the dilute acetic acid solution is (2-5):(5-10):100.

[0048] In one or some possible embodiments, in S12, the mass ratio of the β-cyclodextrin derivative to the nano-silica modified with the silane coupling agent and the buffer solution is (2-5):(5-10):100.

[0049] In one or some possible embodiments, in S13, when placed in a buffer solution containing a β-cyclodextrin derivative, the mixing temperature is set to 40-60° C., and the mixing time is set to 2-4 h.

[0050] In one or some possible embodiments, in S2, the extrusion temperature is set to 170-210°C.

[0051] As another aspect of the present invention, it relates to the application of the above-mentioned polyolefin material, wherein the polyolefin material is used as a drug solution packaging material in the medical field or as a thin-wall injection molding product in the automotive field.

[0052] The invention utilizes the inclusion action of cyclodextrin derivatives on organic molecules, and crosslinks the modified polypropylene molecular chains through the host-guest reaction between the cylindrical molecule β-cyclodextrin and the benzene ring, thereby strengthening the phase interface interaction force and making the polyolefin material have excellent rigidity-toughness balance.

[0053] The present invention introduces a hydrophilic β-cyclodextrin derivative as a modified material to improve the dispersibility of silicon dioxide particles in the resin material, improve the agglomeration problem of the filling particles in the polymer material, and effectively increase the SiO 2 The particles enhance the rigidity of the polypropylene (PP) matrix and significantly improve the impact strength and flexural modulus of the product.

[0054] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 For modified SiO 2 Schematic diagram of the preparation process; wherein, 1) is the activation process; 2) is the modification step of the silane coupling agent; 3) is the modification step of the cyclodextrin derivative;

[0056] Figure 2 Schematic diagram of the structure of β-cyclodextrin derivatives;

[0057] Figure 3 The three silicas (SiO 2 ) particles; wherein the infrared spectrum of activated silicon dioxide B1 is shown in Fig. 2 curve; the infrared spectrum curve of silicon dioxide B2 modified by silane coupling agent is shown in SiO 2 -GOPS curve; infrared spectrum curve of modified silica B modified by cyclodextrin derivatives see SiO 2 -βCD curve;

[0058] Figure 4These are scanning electron microscope images of the polyolefin materials in Comparative Example 1 and Example 3; wherein the left image represents Comparative Example 1, and the right image represents Example 3. DETAILED DESCRIPTION

[0059] The present invention is further described below in conjunction with specific embodiments, and the protection scope of the present invention is not limited by the following embodiments. The sources of the materials mainly involved in the embodiments are shown in Table 1 below, and other materials not shown are conventional commercial products.

[0060] Table 1 Material source description

[0061]

[0062]

[0063] The present invention adopts a twin-screw extruder of model ZSE34 from Leistrize Company of Germany; the high-speed mixer of the present invention is model SHR-500A.

[0064] The polypropylene used in the present invention is the following five kinds:

[0065] Polypropylene 1: copolymerized polypropylene, MFR = 30g / 10min, the mass content of comonomer ethylene is 15%, of which the mass content of ethylene-propylene random copolymer is 24%, the mass content of ethylene-propylene block copolymer is 11%, and the mass content of isotactic polypropylene is 65%. The particle size of the ethylene-propylene random copolymer particles is 0.05-4μm, and the density of the particles is 1×10 8 Pieces / mm 3 .

[0066] Polypropylene 2: copolymerized polypropylene, MFR = 40g / 10min, the mass content of the comonomer ethylene is 10%, of which the mass content of the ethylene-propylene random copolymer is 17%, the mass content of the ethylene-propylene block copolymer is 7%, and the mass content of the isotactic polypropylene is 76%. The particle size of the ethylene-propylene random copolymer particles is 0.05-4μm, and the density of the particles is 1×10 7 Pieces / mm 3 .

[0067] Polypropylene 3: copolymerized polypropylene, MFR = 50g / 10min, the mass content of comonomer ethylene is 8%, of which the mass content of ethylene-propylene random copolymer is 14%, the mass content of ethylene-propylene block copolymer is 5%, and the mass content of isotactic polypropylene is 81%. The particle size of the ethylene-propylene random copolymer particles is 0.05-4μm, and the density of the particles is 1×10 6 Pieces / mm 3 .

[0068] Polypropylene 4: copolymerized polypropylene, MFR = 110g / 10min, the mass content of the comonomer ethylene is 5%, the mass content of the ethylene-propylene random copolymer is 8%, the mass content of the ethylene-propylene block copolymer is 3%, and the mass content of the isotactic polypropylene is 89%. The particle size of the ethylene-propylene random copolymer particles is 0.05-4μm, and the density of the particles is 1×10 5 Pieces / mm 3 .

[0069] Polypropylene 5: homopolypropylene, MFR = 50 g / 10 min.

[0070] In the embodiments of the present invention, the preparation process and reaction conditions of some solutions are as follows:

[0071] Activation solution: Hydrogen peroxide with a mass concentration of 30% and concentrated sulfuric acid are mixed in a volume ratio of (2-3):6. The preparation process is exothermic, and after cooling to room temperature, an activation solution is obtained.

[0072] Reaction solution: A silane coupling agent was added dropwise to a dilute acetic acid solution (acetic acid: water = (3-20): 100, volume ratio), and the mixture was stirred for 1 hour under a nitrogen atmosphere to obtain a reaction solution.

[0073] Buffer solution: The buffer solution is a mixed aqueous solution of 0.1 M 4-morpholineethanesulfonic acid, 0.01 M 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.02 M N-hydroxysuccinimide (pH 5.5).

[0074] Granulation conditions: The extrusion temperature of the twin-screw extruder was set at 170-210°C to obtain a polyolefin material.

[0075] The solution preparation process and reaction conditions in each embodiment are the same and will not be described in detail.

[0076] The inventors have further developed the following examples 1 to 8 to enhance the toughening of polyolefin materials. In the following examples, the preparation process of modified silica B is shown in the attached Figure 1 The structural diagram of the β-cyclodextrin derivative used is shown in the attached Figure 2 .

[0077] Example 1

[0078] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0079] (1) 99.3 parts of polypropylene 1, 0.2 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide were added to an internal mixer and operated at 180° C. and 40 rpm for 10 minutes to obtain modified polypropylene A;

[0080] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 2:6, volume ratio), reacting at 50°C for 2 hours to obtain activated silica B1, immersing the activated silica B1 in a dilute acetic acid solution containing 3-glycidyloxypropyltrimethoxysilane (wherein, the mass ratio of 3-glycidyloxypropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution is 2:5:100; the mass ratio of acetic acid: water in the dilute acetic acid solution is 3:100), reacting at 23°C for 4 hours to obtain silane coupling agent-modified silica B2, immersing the silane coupling agent-modified silica B2 in a buffer solution containing hydroxyethyl-β-cyclodextrin (wherein, the mass ratio of hydroxyethyl-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 2:5:100), reacting at 40°C for 4 hours to obtain modified silica B;

[0081] (3) 95 parts of the modified polypropylene A, 1 part of modified silica B, 2 parts of hydrotalcite, 1 part of antioxidant 1010 and 1 part of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0082] Example 2

[0083] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0084] (1) 98.5 parts of polypropylene 2, 1.0 parts of styrene monomer and 0.5 parts of dicumyl peroxide were added to an internal mixer and operated at 190° C. and 50 rpm for 5 minutes to obtain modified polypropylene A;

[0085] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 2:6, volume ratio), reacting at 60°C for 1 hour to obtain activated silica B1, immersing the activated silica B1 in a dilute acetic acid solution containing 3-glycidyloxypropyltriethoxysilane (wherein, the mass ratio of 3-glycidyloxypropyltriethoxysilane, activated silica B1 and dilute acetic acid solution is 5:10:100; acetic acid: water in the dilute acetic acid solution is 5:100, volume ratio), reacting at 23°C for 2 hours to obtain silane coupling agent-modified silica B2, immersing the silane coupling agent-modified silica B2 in a buffer solution containing hydroxyethyl-β-cyclodextrin (wherein, the mass ratio of hydroxyethyl-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 5:10:100), reacting at 60°C for 2 hours to obtain modified silica B;

[0086] (3) 93 parts of the modified polypropylene A, 3 parts of modified silicon dioxide B, 1 part of calcium stearate, 1 part of zinc stearate and 2 parts of antioxidant 1010 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0087] Example 3

[0088] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0089] (1) 98 parts of polypropylene 3, 1.5 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide were added to an internal mixer and operated at 180° C. and 40 rpm for 10 minutes to obtain modified polypropylene A;

[0090] (2) 20 parts of nano-silica were immersed in 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 2:6, volume ratio), reacted at 50°C for 2 hours to obtain activated silica B1, and the activated silica B1 was immersed in a dilute acetic acid solution containing 3-glycidyloxypropyltrimethoxysilane (wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution was 2:5:100; the dilute acetic acid solution contained acetic acid: water = 5:100, volume ratio). ratio), react at 23°C for 4 hours to obtain silica B2 modified with a silane coupling agent, immerse the silica B2 modified with a silane coupling agent in a buffer solution containing a mixture of hydroxypropyl-β-cyclodextrin, hydroxyethyl-β-cyclodextrin and amino-β-cyclodextrin (wherein, the mass ratio of the mixture of hydroxypropyl-β-cyclodextrin, hydroxyethyl-β-cyclodextrin and amino-β-cyclodextrin, the silica B2 modified with a silane coupling agent and the buffer solution is 2:5:100), react at 40°C for 4 hours to obtain modified silica B;

[0091] (3) 90 parts of the modified polypropylene A, 5 parts of modified silicon dioxide B, 2 parts of calcium stearate, 1 part of antioxidant 1010 and 2 parts of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0092] Example 4

[0093] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0094] (1) 98 parts of polypropylene 3, 1.5 parts of styrene monomer and 0.5 parts of dicumyl peroxide were added to an internal mixer and operated at 190° C. and 50 rpm for 5 minutes to obtain modified polypropylene A;

[0095] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 3:6, volume ratio), reacting at 60°C for 1 hour to obtain activated silica B1, immersing the activated silica B1 in a dilute acetic acid solution containing 3-glycidyloxypropyltrimethoxysilane (wherein, the mass ratio of 3-glycidyloxypropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution is 5:10:100; acetic acid: water in the dilute acetic acid solution is 10:100, volume ratio), reacting at 23°C for 2 hours to obtain silane coupling agent-modified silica B2, immersing the silane coupling agent-modified silica B2 in a buffer solution containing mercapto-β-cyclodextrin (wherein, the mass ratio of mercapto-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 5:10:100), reacting at 60°C for 2 hours to obtain modified silica B;

[0096] (3) 90 parts of the modified polypropylene A, 5 parts of modified silicon dioxide B, 2 parts of calcium stearate, 1 part of antioxidant 1010 and 2 parts of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0097] Example 5

[0098] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0099] (1) 98 parts of polypropylene 3, 1.5 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide were added to an internal mixer and operated at 180° C. and 40 rpm for 10 minutes to obtain modified polypropylene A;

[0100] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 3:6, volume ratio), reacting at 50°C for 2 hours to obtain activated silica B1, immersing the activated silica B1 in a dilute acetic acid solution containing 3-glycidyloxypropyltrimethoxysilane (wherein, the mass ratio of 3-glycidyloxypropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution is 2:5:100; the mass ratio of acetic acid: water in the dilute acetic acid solution is 5:100), reacting at 23°C for 4 hours to obtain silane coupling agent-modified silica B2, immersing the silane coupling agent-modified silica B2 in a buffer solution containing amino-β-cyclodextrin (wherein, the mass ratio of amino-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 2:5:100), reacting at 40°C for 4 hours to obtain modified silica B;

[0101] (3) 92 parts of the modified polypropylene A, 7 parts of modified silicon dioxide B, 0.4 parts of calcium stearate, 0.2 parts of antioxidant 1010 and 0.4 parts of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0102] Example 6

[0103] Refer to the attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0104] (1) 96.5 parts of polypropylene 4, 3.0 parts of styrene monomer and 0.5 parts of dicumyl peroxide were added to an internal mixer and operated at 190° C. and 50 rpm for 5 minutes to obtain modified polypropylene A;

[0105] (2) 20 parts of nano-silica were immersed in 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 2:6, volume ratio), reacted at 60°C for 1 hour to obtain activated silica B1, and the activated silica B1 was immersed in a dilute acetic acid solution containing 3-glycidyloxypropyltrimethoxysilane (wherein the mass ratio of 3-glycidyloxypropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution was 5:10:100; the mass ratio of acetic acid: water in the dilute acetic acid solution was 5:10:100; and the mass ratio of acetic acid: water in the dilute acetic acid solution was 5:10:100). 5:100, volume ratio), react at 23°C for 2 hours to obtain silica B2 modified with a silane coupling agent, immerse the silica B2 modified with a silane coupling agent in a buffer solution containing a mixture of hydroxypropyl-β-cyclodextrin and hydroxyethyl-β-cyclodextrin (wherein, the mass ratio of the mixture of hydroxypropyl-β-cyclodextrin and hydroxyethyl-β-cyclodextrin, the silica B2 modified with a silane coupling agent and the buffer solution is 5:10:100), react at 60°C for 2 hours to obtain modified silica B;

[0106] (3) 88 parts of the modified polypropylene A, 7 parts of modified silicon dioxide B, 2 parts of calcium stearate and 3 parts of antioxidant 1010 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0107] Example 7

[0108] Refer to the attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0109] (1) 96.5 parts of polypropylene 4, 3.0 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide were added to an internal mixer and operated at 180° C. and 40 rpm for 10 minutes to obtain modified polypropylene A;

[0110] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 3:6, volume ratio), reacting at 50°C for 2 hours to obtain activated silica B1, immersing the activated silica B1 in a dilute acetic acid solution containing 3-aminopropyltrimethoxysilane (wherein, the mass ratio of 3-aminopropyltrimethoxysilane, activated silica B1 and dilute acetic acid solution is 2:5:100; the mass ratio of acetic acid: water in the dilute acetic acid solution is 20:100), reacting at 23°C for 4 hours to obtain silane coupling agent-modified silica B2, immersing the silane coupling agent-modified silica B2 in a buffer solution containing carboxymethyl-β-cyclodextrin (wherein, the mass ratio of carboxymethyl-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 2:5:100), reacting at 40°C for 4 hours to obtain modified silica B;

[0111] (3) 86 parts of the modified polypropylene A, 7 parts of modified silica B, 1 part of hydrotalcite, 1 part of calcium stearate, 1 part of zinc stearate, 2 parts of antioxidant 1010 and 2 parts of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polyolefin material.

[0112] Example 8

[0113] See attached Figure 1 and attached Figure 2 The polyolefin material prepared in this embodiment comprises the following steps:

[0114] (1) 96.5 parts of polypropylene 5, 3.0 parts of styrene monomer and 0.5 parts of dicumyl peroxide were added to an internal mixer and operated at 190° C. and 50 rpm for 5 minutes to obtain modified polypropylene A;

[0115] (2) immersing 20 parts of nano-silica into 80 parts of an activation solution (hydrogen peroxide: concentrated sulfuric acid = 2:6, volume ratio), reacting at 60° C. for 1 hour to obtain activated silica B1, immersing activated silica B1 in a dilute acetic acid solution containing 3-aminopropyltriethoxysilane (wherein, the mass ratio of 3-aminopropyltriethoxysilane, activated silica B1 and dilute acetic acid solution is 5:10:100; acetic acid: water in the dilute acetic acid solution is 5:100, volume ratio), reacting at 23° C. for 2 hours to obtain silane coupling agent-modified silica B2, adding silane coupling agent-modified silica B2 into a buffer solution containing hydroxyethyl-β-cyclodextrin (wherein, the mass ratio of hydroxyethyl-β-cyclodextrin, silane coupling agent-modified silica B2 and buffer solution is 5:10:100), reacting at 60° C. for 2 hours to obtain modified silica B;

[0116] (3) 75 parts of the modified polypropylene A, 20 parts of modified silicon dioxide B, 2 parts of calcium stearate, 1 part of antioxidant 1010 and 2 parts of antioxidant 168 were mixed in a high-speed mixer (480 rpm) for 3 minutes and then extruded and granulated to obtain a polypropylene material.

[0117] When conducting experimental research, the inventor prepared comparative examples 1 to 7 by changing some of the set conditions.

[0118] Comparative Example 1

[0119] The difference from Example 3 is that no modified silicon dioxide is added.

[0120] Comparative Example 2

[0121] The difference from Example 3 is that untreated nano-silicon dioxide (nano-SiO 2 ).

[0122] Comparative Example 3

[0123] The difference from Example 3 is that the modified silica used is not modified with a cyclodextrin derivative;

[0124] Comparative Example 4

[0125] The difference from Example 8 is that the polypropylene used is not modified with styrene and the amount of polypropylene is 99.5 parts.

[0126] Comparative Example 5

[0127] The difference from Example 8 is that the modified polypropylene used is prepared from 99.4 parts of polypropylene 5, 0.1 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide.

[0128] Comparative Example 6

[0129] The difference from Example 8 is that the modified polypropylene used is prepared from 94.5 parts of polypropylene 5, 5 parts of styrene monomer and 0.5 parts of di-tert-butyl peroxide.

[0130] Comparative Example 7

[0131] The SiO prepared in this comparative example 2 -g-PMMA hybrid particles refer to "Lu Ping.SiO 2 -g-PMMA / PP nanocomposite material preparation and performance research [J]. Plastics Industry, 2010, 38 (08): 25-28." The specific operation is as follows:

[0132] The SiO 2 After the nanoparticles are modified by alkylation, PMMA is further modified. The preparation process is as follows: Under stirring conditions, alkylated nano-SiO2 Sodium dodecyl sulfate, emulsifier OP-10, and isopropanol were added to deionized water, and then MMA and an aqueous solution containing potassium persulfate were simultaneously dripped into a four-necked bottle, and reacted at 75°C for 4 hours. After 4 hours, the temperature was raised to 90°C and maintained for 30 minutes to obtain SiO 2 -g-PMMA hybrid particles.

[0133] Performance Testing

[0134] The following performance tests were performed on the above Examples 1 to 8 and Comparative Examples 1 to 7, and the test results are recorded in Table 1 below.

[0135] (1) Test - Flexural elastic modulus test

[0136] The test is carried out in accordance with the relevant standards and test procedures in GB / T9341-2008 "Determination of Bending Properties of Plastics";

[0137] (2) Test two simply supported beam notch impact strength test

[0138] The test was carried out in accordance with the relevant standards and test procedures in GB / T1043.1-2008 "Determination of impact properties of simply supported plastic beams";

[0139] (3) Test three load thermal deformation temperature test

[0140] The measurement is carried out in accordance with the relevant standards and test procedures in GB / T 1634.2-2019 "Determination of load deformation temperature of plastics".

[0141] Table 1 Polypropylene material performance test results

[0142]

[0143] From the performance test results of polyolefin materials shown in Table 1, we can find that:

[0144] The composite material made of polypropylene modified with styrene monomer and silica nanoparticles modified with β-cyclodextrin derivatives has excellent rigidity and toughness balance. The obtained polyolefin material has a bending elastic modulus greater than 1200MPa and a simply supported beam notched impact strength greater than 30kJ / m 2 When the polypropylene matrix resin in the present invention adopts copolymerized polypropylene, the product has better impact resistance, and the simply supported beam notched impact strength can reach 50kJ / m 2 above.

[0145] Compared with Example 3, no silica particles are added in Comparative Example 1, so the performance is not improved; the silica particles in Comparative Example 2 are not treated in any way, and agglomerate significantly in the system, resulting in many defects in the composite material, and the product performance is reduced compared with Comparative Example 1. The silica particles in Comparative Example 3 are not modified with cyclodextrin derivatives, so they cannot undergo a cross-linking reaction with modified polypropylene A to improve product performance, but the dispersion of silica in the system is slightly improved, so the bending modulus is slightly improved. Compared with Example 8, the resin matrix in Comparative Example 4 does not contain benzene rings, so no cross-linking reaction occurs in the system, and the simply supported beam notched impact strength of the obtained product is not improved; the amount of styrene monomer used in Comparative Example 5 is relatively small, and the amount of styrene monomer used in Comparative Example 6 is relatively large, and the corresponding mechanical properties are reduced compared with Example 8.

[0146] The inventors have repeatedly verified this phenomenon through multiple experiments and concluded that when the feed amount is less than 0.2%, the grafting rate of styrene monomer is too low, which is not conducive to the cross-linking reaction, resulting in worse impact performance of the product; when the feed amount is greater than 3%, the content of long-chain branches in the system increases, the melt index decreases significantly, which is not conducive to processing, and at this time, the styrene self-polymerization rate increases, which is not conducive to the grafting reaction. By adopting the technical solution of the present invention, the mass of the styrene is controlled to 0.2-3.0% of the mass of the polypropylene, which is conducive to the uniform distribution of the styrene monomer on the copolymerized polypropylene molecular chain, and is conducive to the cross-linking reaction with modified silica B in the later stage, and the mechanical properties of the polypropylene resin are improved under the condition of slightly decreasing the melt flow rate.

[0147] In addition, combined with the preparation steps and attached Figure 3 From the infrared spectrum curves of B1, B2, and B, we can see that: SiO 2 -GOPS sample at 968cm -1 The characteristic peak of epoxy group appeared at 2932cm -1 and 2855cm -1 The characteristic peaks of methyl and methylene appeared at 3423 cm -1 The characteristic peak of the stretching vibration of the hydroxyl group at the SiO2 was significantly weakened, indicating that the silane coupling agent was bonded to some hydroxyl groups, so that the epoxy group was grafted on the SiO2 2 Above; after modification with cyclodextrin derivatives, 968cm -1 The characteristic peak at 1625cm -1 The peak at 3423 cm is the stretching vibration peak of the carbon-carbon double bond. -1 The stretching vibration peak of the hydroxyl group is enhanced because the hydroxyl molecules on the surface of the cyclodextrin molecules enhance the absorption peak here. The above analysis shows that β-cyclodextrin is effectively grafted onto SiO 2 Particle surface.

[0148] Through Example 3 and Comparative Example 1, and in combination with the attached Figure 4 From the scanning electron microscope images of medium-reinforced polypropylene before and after modification, it can be seen that: the xylene soluble cross-section of the resin material before modification has coarse pores in the rubber phase and a clear outline of the interface between the two phases; in the grafted sample, the rubber phase presents a uniform and fine pore structure, with more core-shell structures, irregular cross-section surface, and ductile fracture. The depth of the rubber phase pores becomes shallower, indicating that the content of the rubber phase that can be etched by xylene is reduced, indicating that cross-linking has enhanced the interfacial force between the two phases to a certain extent, the corresponding impact strength is high, and there is no dispersion, the overall performance is stable, and the rubber phase is more evenly distributed.

[0149] In summary, the inventors believe that the flexural modulus and simply supported beam impact strength of the reinforced impact-resistant polypropylene material prepared by adding modified silica nanoparticles are significantly higher than those of the unmodified sample with the same rubber phase content prepared in the comparative example, wherein the increase in the flexural modulus is attributed to the reinforcing effect of the modified particles on the homopolymer phase, and the increase in the impact strength is mainly due to the modified particles located in the compatibilized phase (between the homopolymer phase and the rubber phase) promoting the fusion of the two phases during the processing and enhancing the interaction between the two phases. In addition, the results show that SiO 2 After grafting modification, its nucleation ability is stronger and its heat deformation temperature is higher, which further confirms that the improvement of affinity between particles and matrix is ​​conducive to the improvement of heterogeneous nucleation ability of particles.

[0150] The above are only preferred feasible embodiments of the present invention, and the protection scope of the present invention is not limited thereto. Various modifications or applications made according to the above embodiments are within the protection scope of this technical solution.

[0151] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art. According to all the teachings disclosed, various modifications and replacements can be made to those details, and these changes are all within the protection scope of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A reinforced and toughened polyolefin material, characterized in that: The composition comprises the following raw materials by weight: 75-95 parts of modified polypropylene A, 1-20 parts of modified silicon dioxide B, and 1-7 parts of auxiliary agent; The modified polypropylene A is modified by a grafting monomer, and the structural formula (I) of the grafting monomer is: In formula (I): X is a linear alkyl group containing 1 to 10 carbon atoms or a saturated fatty alcohol group, or does not contain X; The surface of the modified silica B is modified with a cyclodextrin derivative.

2. A reinforced and toughened polyolefin material according to claim 1, characterized in that: The grafting monomer is styrene, and the mass content of the styrene in the modified polypropylene A is 0.2-3%; the cyclodextrin derivative is a β-cyclodextrin derivative, and the mass content of the β-cyclodextrin derivative in the modified silicon dioxide B is 0.5-5%.

3. A reinforced and toughened polyolefin material according to claim 1 or 2, characterized in that: The composition comprises the following raw materials by weight: 88-95 parts of modified polypropylene A, 5-7 parts of modified silicon dioxide B, and 4-5 parts of auxiliary agent; The modified polypropylene A is obtained by modifying polypropylene with styrene, and the mass content of the styrene in the modified polypropylene A is 0.2-3%; The surface of the modified silicon dioxide B is modified by a silane coupling agent and the beta-cyclodextrin derivative in sequence, and the mass content of the beta-cyclodextrin derivative in the modified silicon dioxide B is 0.5-5%.

4. A reinforced and toughened polyolefin material according to claim 3, characterized in that: The polypropylene is homopolypropylene or copolymer polypropylene.

5. The reinforced and toughened polyolefin material according to claim 4, characterized in that: The melt flow rate of the polypropylene material is 30-110 g / 10 min.

6. The reinforced and toughened polyolefin material according to claim 4, characterized in that: The copolymerized polypropylene is selected from ethylene-propylene copolymer, and the mass content of the ethylene monomer in the copolymerized polypropylene is 5-15%.

7. A reinforced and toughened polyolefin material according to claim 6, characterized in that: The mass content of the ethylene monomer is 8-10%.

8. The reinforced and toughened polyolefin material according to claim 6, characterized in that: The copolymerized polypropylene comprises ethylene-propylene random copolymer, ethylene-propylene block copolymer and isotactic polypropylene; the mass content of the ethylene-propylene random copolymer is 8-24%; the mass content of the ethylene-propylene block copolymer is 3-11%; and the mass content of the isotactic polypropylene is 65-89%.

9. The reinforced and toughened polyolefin material according to claim 8, characterized in that: The particle size of the ethylene-propylene random copolymer particles is 0.05 to 4 μm, and the density is 1×10 5 ~1×10 8 Pieces / mm 3 .

10. The reinforced and toughened polyolefin material according to claim 3, characterized in that: The silane coupling agent is selected from one or more of 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and 3-aminopropyltriethoxysilane; The derivative of β-cyclodextrin is selected from one or more of hydroxyethyl-β-cyclodextrin, hydroxypropyl-β-cyclodextrin, amino-β-cyclodextrin, thiol-β-cyclodextrin, carboxymethyl-β-cyclodextrin and β-cyclodextrin.

11. A reinforced and toughened polyolefin material according to claim 1 or 3, characterized in that: The auxiliary agents include halogen absorbers and antioxidants.

12. The reinforced and toughened polyolefin material according to claim 11, characterized in that: The halogen absorbent is selected from one or more of hydrotalcite, calcium stearate and zinc stearate.

13. The reinforced and toughened polyolefin material according to claim 11, characterized in that: The antioxidant is a hindered phenol antioxidant or a compound antioxidant; The compound antioxidant includes a main antioxidant and a secondary antioxidant, wherein the mass ratio of the main antioxidant to the secondary antioxidant is 1:(1-2).

14. The reinforced and toughened polyolefin material according to claim 13, characterized in that: The main antioxidant is a hindered phenol antioxidant; the auxiliary antioxidant is a phosphite antioxidant.

15. A method for preparing the reinforced and toughened polyolefin material according to any one of claims 1 to 14, characterized in that: The method comprises the following steps: S1. Add modified polypropylene A, modified silicon dioxide B and additives in order by weight, mix well, and obtain a prefabricated material; S2, extruding and granulating the prefabricated material in S1 to obtain a polyolefin material.

16. The method for preparing a reinforced and toughened polyolefin material according to claim 15, characterized in that: In S1, the preparation of the modified polypropylene A includes: mixing the polypropylene, the styrene and the initiator to obtain a mixed modified polypropylene A.

17. The method for preparing a reinforced and toughened polyolefin material according to claim 16, characterized in that: The mixing temperature is set to 180-190° C., the rotation speed is set to 40-50 rpm, and the mixing time is 5-10 min.

18. The method for preparing a reinforced and toughened polyolefin material according to claim 15, characterized in that: In S1, the preparation of the modified silicon dioxide B comprises the following steps: S11, placing nano-silicon dioxide in an activation solution to obtain activated nano-silicon dioxide; S12, adding the activated nano-silica in S11 to a dilute acetic acid solution of a silane coupling agent to obtain nano-silica modified with a silane coupling agent; S13, placing the nano-silica modified with a silane coupling agent obtained in S12 in a buffer solution containing a β-cyclodextrin derivative, and mixing them evenly to obtain modified silica B.

19. The method for preparing a reinforced and toughened polyolefin material according to claim 18, characterized in that: In S11, the activation temperature of the activated nano-silicon dioxide is 50-60° C., and the activation time is 1-2 hours.

20. The method for preparing a reinforced and toughened polyolefin material according to claim 18, characterized in that: In S12, the mixing time of the activated nano-silica and the dilute acetic acid solution of the silane coupling agent is 2 to 4 hours.

21. The method for preparing a reinforced and toughened polyolefin material according to claim 18, characterized in that: In S12, the mass ratio of the silane coupling agent to the activated nano-silica and the dilute acetic acid solution is (2-5):(5-10):

100.

22. The method for preparing a reinforced and toughened polyolefin material according to claim 18, characterized in that: In S13, the mass ratio of the β-cyclodextrin derivative to the nano-silica modified with the silane coupling agent and the buffer solution is (2-5):(5-10):

100.

23. The method for preparing a reinforced and toughened polyolefin material according to claim 18, characterized in that: In S13, when placed in a buffer solution containing a β-cyclodextrin derivative, the mixing temperature is set to 40-60° C., and the mixing time is set to 2-4 hours.

24. The method for preparing a reinforced and toughened polyolefin material according to claim 15, characterized in that: In S2, the extrusion temperature is set to 170-210°C.

25. Use of the reinforced and toughened polyolefin material according to any one of claims 1 to 14, characterized in that: The polypropylene material is used as a liquid medicine packaging material in the medical field or as a thin-wall injection molding product in the automotive field.

Citation Information

Patent Citations

  • High impact polypropylene based compound

    CN108026341A

  • Preparation method of polypropylene reinforced plasticized modifier

    CN101585977A

  • High-toughness polypropylene plastic and preparation method thereof

    CN111574801A

  • Modified high-temperature-resistant polypropylene material and preparation method thereof

    CN111909482A

  • Sealing plastic box and processing technology thereof

    CN116023752A